Simulation results for PLATO: a prototype hybrid X-ray photon counting detector with a low energy threshold for fusion plasma diagnostics. (12th January 2017) - Habib, A.; Menouni, M.; Pangaud, P.; Fenzi, C.; Colledani, G.; Moureau, G.; Escarguel, A.; Morel, C.
Abstract: PLATO is a prototype hybrid X-ray photon counting detector that has been designed to meet the specifications for plasma diagnostics for the WEST tokamak platform (Tungsten (W) Environment in Steady-state Tokamak) in southern France, with potential perspectives for ITER. PLATO represents a customized solution that fulfills high sensitivity, low dispersion and high photon counting rate. The PLATO prototype matrix is composed of 16 × 18 pixels with a 70 μ m pixel pitch. New techniques have been used in analog sensitive blocks to minimize noise coupling through supply rails and substrate, and to suppress threshold dispersion across the matrix. The PLATO ASIC is designed in CMOS 0.13 μ m technology and was submitted for a fabrication run in June 2016. The chip is designed to be bump-bonded to a silicon sensor. This paper presents pixel architecture as well as simulation results while highlighting novel solutions.